Evaluation of a modified cleaning procedure in the prevention of carbapenem-resistant Acinetobacter baumannii clonal spread in a burn intensive care unit using a high-sensitivity luminometer. Issue 1 (January 2017) - Casini, B.; Selvi, C.; Cristina, M.L.; Totaro, M.; Costa, A.L.; Valentini, P.; Barnini, S.; Baggiani, A.; Tagliaferri, E.; Privitera, G.
Summary: Background: Enhanced environmental cleaning practices are among the most accepted measures for controlling the spread of carbapenem-resistant Acinetobacter baumannii (CR-Ab). Aim: To evaluate the impact of heightened cleaning on an ongoing CR-Ab outbreak in a burn intensive care unit (BICU) of an Italian teaching hospital, where chlorhexidine–60% isopropyl alcohol was applied as a complementary disinfectant on high-touch surfaces. Methods: Compliance with the microbial limit proposed for the BICU by AFNOR-NF-S90-351 (20 colony-forming units/100cm 2 ) was assessed by plate count, and compared with the results obtained with intracellular adenosine triphosphate (ATP) detection. Genotyping was performed using pulsed-field gel electrophoresis. Findings: During the standard cleaning regimen, three out of 23 samples (13%) gave results over the AFNOR limit and five (21.7%) showed unacceptable ATP levels with 100 relative light units/100 cm 2 as the benchmark limit (sensibility 86.4%, specificity 92.2%). Following improvement of the cleaning procedure, only two samples out of 50 (4%) did not satisfy the microbiological criteria and seven (14%) exceeded the ATP limit. In a successive phase, eight of 30 samples collected showed unacceptable results (27%). Conclusions: Adding chlorhexidine–60% isopropyl alcohol as complementary disinfectant proved to be effective for reducing environmental microbial contamination, ATP levels and CR-Ab infection/colonization in patients admitted to the BICU. Real-time monitoring by ATP assay was useful for managing the cleaning schedule and reducing hospital infections, although the calculated values must be interpreted as cleanliness indicators rather than risk indicators.